Ultrasound is not associated with the presence of systemic autoimmunity or symptoms in individuals at risk for rheumatoid arthritis. Issue 2 (23rd August 2019) - Brulhart, Laure; Alpízar-Rodríguez, Deshiré; Nissen, Michael S; Zufferey, Pascal; Ciubotariu, Ileana; Fleury, Gregory; Lazarou, Ilias; Gabay, Cem; Finckh, Axel
Abstract : Objective: To identify whether musculoskeletal ultrasound (MSUS) abnormalities are associated with specific phases of rheumatoid arthritis (RA) development in individuals at risk of RA. Methods: This is a prospective cohort study of individuals at risk of developing RA, namely first-degree relatives of patients with RA (RA-FDRs) without evidence of established rheumatic disease at inclusion. The inflammatory activity on MSUS was assessed according to a validated score (SONAR). Active MSUS was defined as a total B-mode score greater than 8, including at least one joint with significant synovitis (grade 2 or 3) or significant synovial hyperaemia (Doppler score greater than 1). We used logistic regression to analyse associations between MSUS findings and recognised preclinical phases of RA development, adjusting for other demographic and biological characteristics. Results: A total of 273 RA-FDRs were analysed, of whom 23 (8%) were anticitrullinated protein autoantibodies-positive, 58 (21%) had unclassified arthritis and 96 (35%) had an active MSUS, which was only associated with unclassified arthritis (OR: 1.8, 95% CI 1.0 to 3.3). Conclusion: In individuals at risk of RA, active MSUS was associated with the presence of unclassified arthritis, but not with any of the earlier described phases of RA development. These findings do not support an indiscriminate use of ultrasound in a screening strategy for preclinical RA.